2015
DOI: 10.1590/1516-1439.361514
|View full text |Cite
|
Sign up to set email alerts
|

Pechini Synthesis of Nanostructured Li1.05M0.02Mn1.98O4 (M = Al3+ or Ga3+)

Abstract: ) were prepared by Pechini synthesis using lithium and manganese acetates, citric acid, ethylene glycol, and the respective oxide or acetate of the doping ions in molar ratios of 2.00 (Mn 1.98 + M 0.02 ) to 1.05 Li. The TGA/DTA of the precursor gels showed weight loss/energy relative to crystallization below 450 ºC. From the XRD, a single cubic phase (F D3M ) was identified for the all-doped or undoped oxides after only 2 h calcination. The unit cell parameters a for both aluminum-and gallium-doped oxides calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The slurry mixture was sonicated for 30 min to form a homogeneous solution. Then it was spun (5000 rpm for 5 s) on a platinum plate and, in order to evaporate the solvent, the electrodes were dried at 120 ºC for 24 h in vacuum 20 .…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The slurry mixture was sonicated for 30 min to form a homogeneous solution. Then it was spun (5000 rpm for 5 s) on a platinum plate and, in order to evaporate the solvent, the electrodes were dried at 120 ºC for 24 h in vacuum 20 .…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Xiong et al [ 47 ] studied LMO doping with multiple cations (Cu, Al, and Ti) and established that multiple doping was effective in improving retention capacity at temperatures of 25 °C to 50 °C, maintaining a high rate capability up to 12C (C represents the numerical value of rated capacity of a battery, in Ah) and reducing Mn dissolution. Amaral et al [ 48 ] reported time and temperature effects of thermal treatment for Ga- and Al-doped LMO synthesis. They identified spinel phase formation at a temperature of 750 °C for a calcination time of 2 h and determined that the specific capacity of doped ones was lower than pure spinel.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure to determine the average manganese valence consisted in directly transferring [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . In this case, the blank was a solution containing only NaCH 3 COO and 1,10-phenanthroline, obtained by adding 10 mL of aqueous 10% (m/m) NaCH 3 COO and 0.1% (m/m) 1,10-phenanthroline solutions to a 50 mL volumetric flask and completing its volume with deionized water.…”
Section: Methodsmentioning
confidence: 99%